2004
DOI: 10.1093/aje/kwh108
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Medication Use and Neuroblastoma in Offspring

Abstract: The association between a mother's use of specific medications during pregnancy and lactation and neuroblastoma in her offspring was evaluated in a case-control study. Newly diagnosed cases of neuroblastoma (n=504) in the United States and Canada were identified between 1992 and 1994 at 139 hospitals affiliated with the Pediatric Oncology Group or the Children's Cancer Group clinical trial programs. One age-matched control was sampled from the community of each case by means of random digit dialing. Exposure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
4
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 58 publications
1
58
4
1
Order By: Relevance
“…In this study, codeine use during pregnancy was not found to be associated with infant survival rate, congenital malformation rate, or other adverse pregnancy outcomes, except for Cesarean delivery and excessive postpartum hemorrhage. Unlike previous studies [4,5,7,8] and other medical literature sources that rely either on data regardng opioid analgesic use in general or a few case studies [9,13], we found no increased risk of congenital malformations or neonatal respiratory depression. Associations of codeine use during pregnancy and neonatal abstinence syndrome were unfortunately not feasible to evaluate, as neonatal abstinence syndrome scores were not routinely applied.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In this study, codeine use during pregnancy was not found to be associated with infant survival rate, congenital malformation rate, or other adverse pregnancy outcomes, except for Cesarean delivery and excessive postpartum hemorrhage. Unlike previous studies [4,5,7,8] and other medical literature sources that rely either on data regardng opioid analgesic use in general or a few case studies [9,13], we found no increased risk of congenital malformations or neonatal respiratory depression. Associations of codeine use during pregnancy and neonatal abstinence syndrome were unfortunately not feasible to evaluate, as neonatal abstinence syndrome scores were not routinely applied.…”
Section: Discussioncontrasting
confidence: 98%
“…One casecontrol study of 504 children with neuroblastoma found an association with in utero exposure to codeine [odds ratio (OR) 3.4, 95% confidence interval (CI) 1. 4-8.4] [4]. Another of 599 infants found that mothers who gave birth to infants with cleft palate or cleft lip with or without cleft palate used opioid analgesics (mainly codeine) much more frequently than the control group; the largest difference was seen for codeine use during the first trimester (8.6% compared with 2.1% of infants in the control group; P< 0.01) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying etiology of most neuroblastoma tumors remains unknown, and although environmental factors have been suggested as possible causes, direct linkage has not been clearly established [11][12][13]. The vast majority of neuroblastoma tumors occur in isolation in families, suggesting that the rates of oncogenic germline mutations in patients with neuroblastoma are low.…”
Section: Epidemiology and Geneticsmentioning
confidence: 99%
“…Studies have examined prenatal exposure to maternal tobacco, [4][5][6][7][8] alcohol, 4,5,7,9,10 maternal hair dye 5,11 and drug-use. 5,7,[12][13][14][15] Other commonly examined exposures include those pertaining to sociodemographics, reproductive and pregnancy history, labor and delivery, and infant characteristics. 6,8,9,12,[16][17][18][19][20][21] To gain further understanding of whether perinatal exposures are involved in the etiology of NB, we evaluated associations between factors recorded in birth records and NB in a populationbased case-cohort study in Minnesota using prospectively collected exposure information.…”
mentioning
confidence: 99%